Developing “KUPANCAR”: A Guidebook and A Collection of Arabic-Speaking Host Texts to Enhance Students' Speaking Skills - Nuriyatul Hidayah; Muhaiban Muhaiban; Hanik Mahliatussikah; Nur Ain Hannani Binti Hamid (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2021)
Enhancing the skills of Arabic-speaking hosts in Indonesia is very important. This study aimed to describe the development process, the validity level, and the effectiveness of "KupANCAR: A Guidebook and a Collection of Arabic-Speaking Host Texts". The KUPANCAR book has innovations in theoretical and practical material, a collection of updated texts, and a QR Code of interesting videos of Arabic-language hosts. This research and development method was The results of the Paired Samples Test revealed that p = 0.000 0.05, the pre-test score reached 0.121, and the post-test score reached 0.114. Thus, it can be summed up that there is a significant difference between the pre-test and post-test scores. It means the student's Arabic speaking skills increased significantly after using KUPANCAR.